A STUbL wards off telomere fusions - Chung, Inn (European Molecular Biology Organization, 2013)
EMBO J (2013) 32: 805–815 doi:; DOI: 10.1038/emboj.2013.24; published online 02 15 2013 Protection of chromosomal ends from erroneous recognition as double-strand breaks (DSBs) is critical for maintaining genome integrity. Unprotected ends can activate DNA repair pathways leading to catastrophic fusions or rearrangements of chromosomes. A study in The EMBO Journal identifies Uls1 as a new player in this end-protection process, utilizing SUMO and ubiquitin modifications to prevent chromosomal fusions by clearing a polysumoylated form of Rap1.